Single Index Model dalam Pemilihan Saham Optimal - Jhonni Sinaga; Aurlia Hayatunisa; Supriyanto Supriyanto (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
This study aims to analyze the optimal stock selection on the Indonesia Stock Exchange using the Single Index Model method, focusing on stocks included in the LQ45 index during the 2019-2023 period. The selection of data samples used in this study is Purposive Sampling and the analysis technique in this study is quantitative descriptive analysis. Based on the results of the analysis, 15 stocks were selected that were included in the LQ45 index category. The results of the study showed that from a sample of 15 stocks, there were 2 stocks that fell into the optimal stock criteria, namely Adaro Energy Tbk (ADRO) and Bank Central Asia Tbk (BBCA), these stocks had an overall Expected Return (ER) of 3.95% and an overall Variance of 2.447%.